WORLD WAR I IN KOREA - Kadirova daughter of Mukhlisa Abdumurad (Galaxy International Interdisciplinary Research Journal, 2023)
"Let’s assume that today we will return to solving the emerging problems only through peace and political negotiations, preventing the ever-increasing tensions, conflicts and contradictions in the international arena, preventing the ongoing bloodshed. , in the words of our people, the world would be a flower" (I.Karimov).